Association of nonalcoholic fatty liver disease and carotid media‐intima thickness: A systematic review and a meta‐analysis - Manouchehr Khoshbaten; Sepideh H. Maleki; Sara Hadad; Amrit Baral; Ana V. Rocha; Laxmi Poudel; Alireza Abdshah (Health Science Reports, 2023)
Abstract Introduction The relationship between cardiovascular disorders and nonalcoholic fatty liver disease (NAFLD) has been extensively studied. To better pool this data and make a more definite conclusion, we performed a meta‐analysis to evaluate the association between NAFLD and the thickness of media and intima of carotid artery (CIMT) and cardiovascular disorders. Methods We searched PubMed, Ovid, Scopus, ProQuest, Web of Science, and the Cochrane Library, and analyzed the pooled data using R studio and the “metafor” package. Results The final analysis included a total of 59 studies with 16,179 cases and 26,120 control individuals. NAFLD was shown to be associated with an increase of 0.1231 mm (20.6%) in carotid artery intima‐media thickness (CIMT) (p = 0.002, 95% confidence interval [CI]: 0.0462–0.2000) in individuals with NAFLD. The prevalence of atherosclerotic plaques in the carotid arteries and the occurrence of NAFLD are significantly correlated, according to a meta‐analysis based on 17 distinct studies (p = 0.001, 1.28–1.43, 95% CI, odds ratio = 1.356). Conclusion Patients with increased CIMT are considerably more likely to have NAFLD. Large prospective investigations are required to corroborate these findings and their prognostic significance, along with the effectiveness of the available interventions.